Antigen-presenting human B cells are expanded in inflammatory conditions. Issue 2 (17th August 2016) - Shimabukuro-Vornhagen, Alexander; García-Márquez, María; Fischer, Rieke N; Iltgen-Breburda, Juliane; Fiedler, Anne; Wennhold, Kerstin; Rappl, Gunter; Abken, Hinrich; Lehmann, Clara; Herling, Marco; Wolf, Dominik; Fätkenheuer, Gerd; et al.
Abstract: Traditionally, B cells have been best known for their role as producers of antibodies. However, in recent years, a growing body of evidence has accumulated showing that B cells fulfill a range of other immunologic functions. One of the functions that has attracted increasing attention is the capacity of B cells to induce antigen-specific activation of T cells through presentation of antigens. However, the analysis of this B cell function has been hampered by the lack of a phenotypically well-defined antigen-presenting B cell subset. Here, we report the identification of a human antigen-presenting B cell subset with strong immunostimulatory properties. This B cell subset is characterized by low expression of CD21 and high expression of the activation marker CD86 and exhibits strong T cell–stimulatory activity, as demonstrated by means of an autologous mixed-lymphocyte reaction. Phenotypically, CD21 low CD86 pos immunostimulatory B cells (BAPC ) represented CD27 + class-switched IgM neg IgD neg B lymphocytes and displayed a higher expression of cell surface receptors, which mediate the migration from peripheral blood to sites of inflammation. Flow cytometric analysis of peripheral blood obtained from individuals with inflammatory conditions revealed that the BAPC subset was expanded following vaccination and in patients with rheumatoid arthritis. Taken together, our work shows that BAPC represents a strongly immunostimulatory B cell subset, which could be a promising target for immunotherapeutic intervention in inflammatory diseases.